2022
DOI: 10.1128/spectrum.00247-22
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Habitat-Dependent Antibiotic Resistance in Pseudomonas aeruginosa

Abstract: Predicting evolution toward antibiotic resistance (AR) and its associated trade-offs, such as collateral sensitivity, is important to design evolution-based strategies to tackle AR. However, the effect of nutrients' availability on such evolution, particularly those that can be found under in vivo infection conditions, has been barely addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 114 publications
3
18
0
Order By: Relevance
“…In former studies, we have determined that P. aeruginosa PA14 populations acquire collateral sensitivity to fosfomycin when subjected to adaptive laboratory evolution (ALE) in the presence of various antibiotics [ 27 , 28 ], tobramycin being one of the most appealing, given its prominent role in antipseudomonal therapies [ 29 ]. Further, we corroborated the robustness of this trade-off in diverse tobramycin-resistant clones of this strain, although its emergence was contingent on the growth conditions [ 30 , 31 ]. Our results indicated that collateral sensitivity to fosfomycin was caused by a lower expression level of P. aeruginosa ’s intrinsic mechanisms of fosfomycin resistance.…”
Section: Introductionsupporting
confidence: 65%
“…In former studies, we have determined that P. aeruginosa PA14 populations acquire collateral sensitivity to fosfomycin when subjected to adaptive laboratory evolution (ALE) in the presence of various antibiotics [ 27 , 28 ], tobramycin being one of the most appealing, given its prominent role in antipseudomonal therapies [ 29 ]. Further, we corroborated the robustness of this trade-off in diverse tobramycin-resistant clones of this strain, although its emergence was contingent on the growth conditions [ 30 , 31 ]. Our results indicated that collateral sensitivity to fosfomycin was caused by a lower expression level of P. aeruginosa ’s intrinsic mechanisms of fosfomycin resistance.…”
Section: Introductionsupporting
confidence: 65%
“…More recently, a novel type of collateral sensitivity has been explored (Hernando-Amado et al, 2023). It has been described that the overexpression of the MexCD-OprJ P. aeruginosa efflux pump, due to mutations in nfxB, which encodes its negative regulator of expression, besides providing resistance to chloramphenicol, tetracyclines and quinolones, is associated with collateral sensitivity to aminoglycosides (Hernando-Amado, Laborda, et al, 2022aLaborda, et al, , 2022bHernando-Amado, López-Causapé, et al, 2022;Imamovic et al, 2018;Mulet et al, 2011). Recent work has shown that the same collateral sensitivity can be achieved just by inducing the expression of the efflux pump, without the need of selecting antibiotic-resistant mutants, an obvious risk in therapy (Hernando-Amado et al, 2023).…”
Section: E Volution -Dri Ven Approaches To Curb Antibiotic Resistancementioning
confidence: 99%
“…The exploration of these changes may serve to find out useful metabolic adjuvants (see below). The other is the identification of specific antibiotics that select mutants presenting unstable resistance phenotypes, ideally linked to stable collateral sensitivity patterns, in the absence of antibiotics (Hernando-Amado, Laborda, et al, 2022aLaborda, et al, , 2022bHernando-Amado, López-Causapé, et al, 2022).…”
Section: E Volution -Dri Ven Approaches To Curb Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study indicated that fitness costs for resistance in surfaceassociated E. coli biofilms did not differ from those in planktonic cultures 79 . In addition, another recent study has shown that the specific environment co-determines fitness and resistance levels associated with specific mutations 131 . Clearly more work is needed to gain deeper insight in parameters affecting fitness in different (structured) environments.…”
Section: Looking At Biofilm Antimicrobial Susceptibility Through the ...mentioning
confidence: 99%